Absolute essentials of green business - Sitkin, Alan (Routledge, 2020)
This short textbook provides a core understanding of the intersection between business and the natural environment. The sector's rapid expansion means that many university programmes are focusing to a greater extent nowadays on the career opportunities generated by the ecological imperative - a curriculum increasingly referred to as "green business". Climate breakdown is a devastating issue facing contemporary society. With six out of the ten largest multinationals listed in the 2018 Fortune Global 500 being active in the energy sector, it is no surprise that more and more business schools are offering modules addressing the management of natural resources. The business world has made some progress incorporating green principles into their strategies and operations, but progress needs to accelerate in line with global agreements to prevent catastrophic ecological and environmental problems. Absolute Essentials of Green Business stands out because of its singular focus on a subset of this wider curricular area. By covering both the macro (framework) and micro (business strategy) aspects of the topic, the book's structure is in line with the way modules of this nature are taught in universities today. Students of business and environmental studies will benefit from reading this concise textbook in order to develop their understanding of a fundamental element of the social science curriculum
Keywords: Business enterprises -- Environmental aspects.; Management -- Environmental aspects.; Green marketing.; Green products.; elektronické knihy; electronic books